The role of One Welfare in development and nutrition security - Doyle, Rebecca; Alders, R. (Informa UK Limited, 2021)
This chapter aims to spark consideration on animal welfare in situations where the development and food security of people is compromised. Improving the opportunities, livelihoods and nutrition security of people often, and rightly, involves the use of animals. Considering animal welfare in these projects where animal-focused outcomes are secondary to people-focused outcomes can help address both short- and long-term challenges and enhance impact. Drawing on published literature and in-depth case studies of current work, examples throughout this chapter illustrate how One Welfare can be a framework for human, animal and environmental improvement in situations where resources and opportunities for people are severely constrained. Towards the end of this chapter, some practical considerations to initiate ideas about ways that an animal welfare-sensitive approach could be included in development and human food security projects are provided. Considering animal welfare in human development actions can lead to sustained benefits to human development and food security.